2022
DOI: 10.1590/fst.63220
|View full text |Cite
|
Sign up to set email alerts
|

Isolation, molecular and phylogenetic identification of microorganisms from Kombucha solution and evaluation of their viability using flow cytometery

Abstract: Kombucha can be produced by coculture of a consortium of bacteria and fungi in a sweetened black tea. Determining the type of microbial population as well as their survival is important because they lead to beneficial and sensory properties of the product. In this study, microorganisms were isolated from kombucha and identified using culture and molecular methods and vacuum dried. Also total phenol content, and antioxidant properties of beverage were characterized. Microorganism viability and sensory evaluatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 43 publications
0
2
0
1
Order By: Relevance
“…Fermentation of kombucha tea involves metabolic activities between yeasts and acetic acid bacteria that utilize substrates in different ways (Teoh et al, 2004;Chakravorty et al, 2016;Jafari et al, 2021). The metabolic relationship of these microorganisms during fermentation produces beneficial organic acids and other substances such as acetic, gluconic acid, glucuronic acid, citric acid, lactic acid, malic acid, succinic acid, saccharic acid, pyruvic acid, sugars, vitamins, and amino acids (Jayabalan et al, 2014;Lee et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Fermentation of kombucha tea involves metabolic activities between yeasts and acetic acid bacteria that utilize substrates in different ways (Teoh et al, 2004;Chakravorty et al, 2016;Jafari et al, 2021). The metabolic relationship of these microorganisms during fermentation produces beneficial organic acids and other substances such as acetic, gluconic acid, glucuronic acid, citric acid, lactic acid, malic acid, succinic acid, saccharic acid, pyruvic acid, sugars, vitamins, and amino acids (Jayabalan et al, 2014;Lee et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The sequences comprising the total reads corresponded to 7 phyla, 39 genera, and 77 species in Kombucha. The overall microbial diversity was higher than the findings of previous studies (Jafari et al, 2022;Torán-Pereg et al, 2021). The results indicated that the metagenomic approach may generate a more complete microbiota profile with enhanced taxonomic resolution and precision in analyzing microbial community in foods when compared with culture-dependent methods (Zhang et al, 2022).…”
Section: Metagenomic Analysismentioning
confidence: 55%
“…A composição da microbiota é fundamental para a qualidade da kombucha; sendo assim, a quantificação dos grupos microbianos majoritários é um parâmetro importante a ser avaliado (JAFARI et al, 2021). Colônias de leveduras, BAL e BAA crescidas em ágar após execução da técnica de drop plate podem ser observadas na Figura 6.…”
Section: Naunclassified